The Impact of Ischemic Stroke on Gray and White Matter Injury Correlated With Motor and Cognitive Impairments in Permanent MCAO Rats: A Multimodal MRI-Based Study - Yang, Le; Li, Manzhong; Zhan, Yu; Feng, Xuefeng; Lu, Yun; Li, Mingcong; Zhuang, Yuming; Lei, Jianfeng; Zhao, Hui (Frontiers in Neurology, 2022)
Background Identifying the alterations of the cerebral gray and white matter is an important prerequisite for developing potential pharmacological therapy for stroke. This study aimed to assess the changes of gray and white matter after permanent middle cerebral artery occlusion (pMCAO) in rats using magnetic resonance imaging (MRI), and to correlate them with the behavior performance. Methods Rats were subjected to pMCAO or sham surgery and reared for 30 days. Motor and cognitive function of the rats were examined by gait and Morris water maze (MWM) tests, respectively. Multimodal MRI was conducted to examine the functional and structural changes of the gray and white matter followed with luxol fast blue (LFB) staining. Results The gait and MWM tests revealed significant motor and cognitive dysfunction in pMCAO rats, respectively. Magnetic resonance angiography presented abnormal intracranial arteries in pMCAO rats with reduced signal intensity of the anterior cerebral artery, anterior communicating cerebral artery, internal carotid artery, and increased basilar artery vessel signal compared with sham rats. Arterial spin labeling confirmed the decreased cerebral blood flow in the infarcted sensorimotor cortex and striatum. Structural T2-weighted imaging and T2 mapping showed brain atrophy and elevation of T2 value in the gray (sensorimotor cortex, striatum) and white (external capsule, internal capsule) matter of pMCAO rats. The results from diffusion tensor imaging (DTI) corresponded well with LFB staining showing reduced relative FA accompanied with increased relative AD and RD in the gray and white matter of pMCAO rats compared with sham rats. Fiber tracking derived from DTI further observed significantly reduced fiber density and length in the corresponding brain regions of pMCAO rats compared with sham rats. Specially, the DTI parameters (especially FA) in the relevant gray matter and white matter significantly correlated with the behavior performance in the gait and MWM tests. Conclusion Collectively, the gray and white matter damages could be non-invasively monitored in pMCAO rats by multimodal MRI. DTI-derived parameters, particularly the FA, might be a good imaging index to stage gray and white matter damages associated with post-stroke motor and cognitive impairments.